Analysis of the biocompatibility of a biocelulose and a poly L-lactic acid membrane - Neto, José Doval; Marques, Rodrigo Fernando Costa [UNESP]; Motta, Adriana Cristina; de Rezende Duek, Eliana Aparecida; de Oliveira, Guilherme José Pimentel Lopes; Marcantonio, Cláudio (Universidade Estadual de Campinas, 2021)
The use of selective barriers as resorbable membranes has become a routine clinical procedure for guided bone regeneration. Therefore, the production of membranes with a low inflammatory potential during their resorption process has become the goal of a considerable number of researches. Aim: The purpose of the present study was to evaluate the biocompatibility of poly (L-lactic acid) (PLLA) and biocelulose membranes (BC) inserted in the subcutaneous tissue on the dorsum of rats. Methods: Fifteen animals underwent surgical procedures for the insertion of 4 types of membranes: COL (Collagen membrane) – Control Group; BC (Biocellulose membrane); BCAg (Biocellulose membrane impregnated with Silver); PLLA (Poly (L-lactic acid) membrane). All membrane types were inserted into each animal. Animals were euthanized after 3, 7, and 15 days of the surgical procedure. Descriptive histological analyses were carried out to investigate host tissue reaction to membrane presence by assessing the anti-inflammatory process composition associated with the membrane resorption and the presence of foreign-body reaction or encapsulation. Results: The BC membranes showed a higher degree of inflammation and poor pattern of integration with the surrounding tissues than the PLLA and COL membranes. Conclusion: The PLLA and COL membranes present better biocompatibility than the BC membranes.
Keywords: Biocompatible materials; Celulose; Inflammation; Membranes; Polyesters